Placental Responses to Changes in the Maternal Environment Determine Fetal Growth - Dimasuay, Kris Genelyn; Boeuf, Philippe; Powell, Theresa L.; Jansson, Thomas (Frontiers in Physiology, 2016)
Placental responses to maternal perturbations are complex and remain poorly understood. Altered maternal environment during pregnancy such as hypoxia, stress, obesity, diabetes, toxins, altered nutrition, inflammation, and reduced utero-placental blood flow may influence fetal development, which can predispose to diseases later in life. The placenta being a metabolically active tissue responds to these perturbations by regulating the fetal supply of nutrients and oxygen and secretion of hormones into the maternal and fetal circulation. We have proposed that placental nutrient sensing integrates maternal and fetal nutritional cues with information from intrinsic nutrient sensing signaling pathways to balance fetal demand with the ability of the mother to support pregnancy by regulating maternal physiology, placental growth, and placental nutrient transport. Emerging evidence suggests that the nutrient-sensing signaling pathway mechanistic target of rapamycin (mTOR) plays a central role in this process. Thus, placental nutrient sensing plays a critical role in modulating maternal-fetal resource allocation, thereby affecting fetal growth and the life-long health of the fetus.